Assessing the Effectiveness of Vegetated Drains in UTHM, Parit Raja - Ismail, Muhammad Aqil Hakimi; Ahmad, Noor Aliza (Journal of Advancement in Environmental Solution and Resource Recovery, 2026)
Vegetated drains are a type of green infrastructure that uses vegetation to capture, infiltrate, and filter stormwater runoff. The study aims to evaluate the performance of vegetated drains in reducing flood risk and improving water quantity in UTHM. Site investigation was at vegetated drains located near the Tunku Tun Aminah Library in UTHM. With hydraulic and statistical analyses, the research evaluates the performance of vegetated drains in reducing peak flow rates, improving infiltration, and enhancing water quantity. Results indicate that vegetated drains effectively reduce peak discharge rates and enhance water infiltration, contributing to flood risk reduction. The analysis highlights that vegetated drains in downstream sections accumulate higher discharges due to upstream contributions and wider channel design. From sample calculation, value of Qdrain for section A and B are both 0.3260 m3/s and 0.3638 m3/s while the value of Qpeak is 0.17 m3/s. Based on result obtained, Qdrain for both section is higher than Qpeak that indicate drainage system is capable of handling the peak flow without overflowing. Factors such as vegetation density, drain geometry, and rainfall intensity significantly influence hydraulic performance. Vegetated drains are a viable, sustainable solution for stormwater management, offering cost-effective maintenance, enhanced water quality, and improved biodiversity while mitigating urban flooding risks.